The Secret Reasons for the Western Scholars Studies The Biography of the prophet (Journal of the College of Education for Women, 2019)
Western Scholars have criticized al the material on the point of reliability . Some have taken the unduly Sceptical view that nothing is to be trusted except Quran . The present study is based on opposing view that at least the material in the early biographers is to be accepted as true , except where there are particular reasons for thinking that an anecdote has been distorted ( or invented ) through legal or political motives. It is also assumed that most of the background material culled from a large number of vaired works , is sound . This standpoint .I would claim , leads to a coherent view of Muhammad's life and achievement.